2010
DOI: 10.1097/pcc.0b013e3181b0655e
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist in children: An observational study

Abstract: We feel that neurally adjusted ventilatory assist would be safe and potentially efficacious to ventilate infants and children. It has the potential for improved patient-ventilator synchrony, decreasing airway pressures, and it might lead to earlier extubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 15 publications
9
58
0
Order By: Relevance
“…These results are in line with studies in adults that all reported similar synchrony improvement with NAVA (5,11,12,20,21). In the pediatric population, no study has yet quantified the trigger delays and cycling-off delays during conventional ventilation and during NAVA, although two feasibility studies have demonstrated that during NAVA, at least two-thirds of assisted breaths were triggered by the neural signal (17,18). A recent study in a heterogeneous pediatric population showed, similar to our findings, that the inspiratory and expiratory phases of the ventilator match the neural phases of the patient better during NAVA (91% of the time was synchronous) as compared with PCV or pressure-regulated volume-control mode (66% of the time was synchronous) (19).…”
Section: Nava In Infantssupporting
confidence: 75%
See 1 more Smart Citation
“…These results are in line with studies in adults that all reported similar synchrony improvement with NAVA (5,11,12,20,21). In the pediatric population, no study has yet quantified the trigger delays and cycling-off delays during conventional ventilation and during NAVA, although two feasibility studies have demonstrated that during NAVA, at least two-thirds of assisted breaths were triggered by the neural signal (17,18). A recent study in a heterogeneous pediatric population showed, similar to our findings, that the inspiratory and expiratory phases of the ventilator match the neural phases of the patient better during NAVA (91% of the time was synchronous) as compared with PCV or pressure-regulated volume-control mode (66% of the time was synchronous) (19).…”
Section: Nava In Infantssupporting
confidence: 75%
“…In the pediatric population, NAVA has been shown to be feasible (17,18) and to be more in phase with the patient's breathing (19). In none of these studies was a specific evaluation performed on the timing differences between the patient and the ventilator on a breath-by-breath basis.…”
mentioning
confidence: 99%
“…30,31 Observational data from small populations suggest that NAVA in these patients is feasible and seems well tolerated. 32,33 …”
Section: Titration Of the Peep Level And Tonic Diaphragm Activitymentioning
confidence: 99%
“…The advantages of NAVA in this regard have been demonstrated in several studies in children [52,55,57]. A prospective crossover study in which NAVA (neural trigger) was compared to pressure support ventilation (pneumatic trigger) demonstrated reduced peak airway pressures with the NAVA mode and elements for a lung protective effect [52].…”
Section: Improving Patient-ventilator Synchronymentioning
confidence: 99%